Les immigrés, rescapés d’un génocide, sont des émigrés de nulle part - Janine Altounian (Amnis)
From an experience which is familiar to me, this paper deals with a type of immigration, paradoxical in its terms since its reference place does not exist any more and is not registered any more in the world as having ever existed: that of the descendants of survivors of the Armenian genocide who, abandoning Constantinople in the 20s, landed in Marseilles as political refugees and imported manpower, provided with a passport being marked “without possible return”.